Exploring effective learning strategies in Arabic language through the ARCS model / Asma’ Ammar ... [et.al] - Ammar, Asma’; Md Sallehuddin, Nur Hakimah; Amat Suparia, Fariz Azzuan; Mohammed Raffi, Muhammad Syaffiq (UiTM Cawangan Johor, 2024)
Learning a foreign language is challenging for non-native speakers. Thus, choosing the best Language Learning Strategies (LLS) is important in learning a foreign language, especially for the Arabic language. The LLS used will be able to help the students to motivate and enhance the language learning to the optimal level. This study aims to investigate the outcome of the Attention, Relevance, Confidence, and Satisfaction Model (ARCS Model) in Arabic language student's learning strategies. A quantitative survey consisting of 41 questions was divided into four sections: demographic profile, attention and relevance, confidence, and satisfaction. The survey was distributed to 182 respondents who took Arabic as a third language in a public university. The data was analysed using SPSS Frequency Statistics. The findings of this study showed there are connections between all three ARCS items. Regular attendance to class and help-seeking in satisfaction components of the ARCS Model indicate the highest mean score. To gain attention and relevance, the majority of students use to find key ideas and connect them to prior knowledge as LLS. In addition, students prefer to reread the materials to develop confidence in learning Arabic. This study helps educators deepen their understanding of the best LLS in teaching and learning Arabic based on the most preferable strategies chosen by the students.